Satisfaction of patients’ needs in the Emergency Department - Metevelis, Evangelos; Marvaki, Christina; Govina, Ourania; Papageorgiou, Dimitrios (Health & Research Journal, 2017)
Introduction: In the modern healthcare systems of the developed countries, patients’ need for more quality health services is strong. Patient satisfaction is an important indicator of the quality of services provided by the Emergency Departments. Aim: The measurement of satisfaction of the patients’ needs by the health services provided at the Emergency Department. Material and Methods: The studied sample consisted of 128 patients who arrived at the Emergency Department of a private clinic. For data collection a special designed questrionnaire was used. Results: The quality of the provided health services is determined by objective criteria related to the consistency and the duration of the services, and the personnel’s capacity to respond to the patient’s needs, part of which are the co-ordination, the politeness and the good communication. 46,1% were men and 53.9% were women. 50 % were married and 56.3% mentioned that they were in good shape.72.7% had not been hospitalized for the past 12 months. The correlation between age and the first 23 questions showed (p<0,019). In addition, there was important correlation between the sex of the patients and the first 23 questions with (p<0,05). Conclusions: The most determined factors for the patients’ satisfaction were proven the easy access to the Emergency Department, in connection with little waiting and a nice environment, and the immediate response of the medical-nursing personnel, which is reflected, apart from its scientific grounding, in its politeness, calmness, discretion and securing of privacy.